(untitled) (Baghdad Science Journal, 2013)
Bacteriophage of E. Coli interspecies from sewage samples were isolated , the phage particles were isolated from two different sewage samples . The first sample was collected from sewage sample of Baghdad university and the second sample was isolated from domestic sewage sample , first sample showed phages specialized for three E. Coli interspecies bacteria (first plate ) and two E. Coli interspecies bacteria (second plate ) , meanwhile second sample showed phage specialized for two E. Coli. interspeciesThe study of appearance of E coli phages from first sample showed three types of E. coli phages with different size of inhibition zone ( 1 , 0.7,0.5 )Cm respectively ( first plate ) , meanwhile E. Coli interspecies bacteria showed phages related with two interspecies with size of inhibition zone ( 0.5 ,0.4) Cm respectively ( second plate ), on other hand , the second sample showed also two interspecies E. coli with inhibition zone (1,0.8)Cm . experimental method has been designed which showed the modifying method of phage assay to determine phage typing assay . phage has been tested particles with different bacterial strains ( E. coli , shagilla and Serratia ) from different sources and the control was the host of each bacteriophages by taking the O.D for all the tests and controls , to setup new criteria for phage typing .:and this test is called ( Clearance Test ) The result showed that O.D for Test 1 , 2 , 3, was ( 1.6 , 1.2 . 1.7) for ( E. coli , shagilla and Serratia ) bacterial strains , meanwhile the control tests was ( 0.3 , 0.2, 0.4 ) for strains isolated from first sample (first and second plate ) and second samples with different interspecies respectively . This result can predict high specificity of phage strain and this method can be used to determine interspecies strains .So from this experiment we can identify only Clearance Test by measuring only O.D. of bacterial strain with different phages instead of going through plaque assay .